Praktik Pemasaran Digital di Hotel Jimbarwana Jembrana Bali - Rahmat Hidayat; I Made Darma Oka; Ni Gst Nym Suci Murni (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze and formulate an ideal digital marketing innovation model to increase occupancy at the Jimbarwana Hotel in Jembrana Regency. Using quantitative and qualitative (explanatory) approaches, this study examines five types of digital marketing: website, social media, SEO, email marketing, and online advertising. The quantitative analysis shows that all types of digital marketing have a significant influence on digital marketing innovation. Specifically, website (0.221) and online advertising (0.218) have a very strong influence, followed by social media (0.207), email marketing (0.242), and SEO (0.236). Furthermore, digital marketing innovation is proven to have a very strong and significant influence on digital marketing effectiveness (0.779). The qualitative analysis strengthens these findings by identifying key strategies for each digital element. The website is seen as the